Sistem Ekonomi Islam Simbol Kesejahteraan Masyarakat - Muhammad Wildan; Muhammad Wildan (el-Jizya : Jurnal Ekonomi Islam, 2018)
The term â€œeconomyâ€ comes from Greek word â€œoikonomiaâ€ consisting of â€œoikosâ€ which means household and â€œnomosâ€ which means regulation. The word â€œoikonomiaâ€ can be defined as the applicable regulation to fulfill the needs in a household. Islamic economics aims to build the economic independence of society collectively, meanwhile conventional economics is still individualistic. In the amidst of globalization, the efforts of sharia economist in covering coventional economic flow are already good enough. System that is already ingrained in society cannot easily be changed. The good strategic plan is required in instilling Islamic economic system in the middle of society. Thomas Kuhn says: â€every system has paradigm and the core of Islamic economic paradigm is definitely from Qurâ€™an and Sunnahâ€.